Potential roles of cytokines and chemokines in human intervertebral disc degeneration: interleukin-1 is a master regulator of catabolic processes. Issue 7 (July 2015) - Phillips, K.L.E.; Cullen, K.; Chiverton, N.; Michael, A.L.R.; Cole, A.A.; Breakwell, L.M.; Haddock, G.; Bunning, R.A.D.; Cross, A.K.; Le Maitre, C.L.
Summary: Objective: These studies investigated cytokine and chemokine receptor profiles in nucleus pulposus (NP) cells, and the effects of receptor stimulation on mRNA levels of extracellular matrix (ECM) components, degrading enzymes and cytokine and chemokine expression. Method: Immunohistochemistry (IHC) was performed to localise expression of CD4, CCR1, CXCR1 and CXCR2 in human NP tissue samples. Effects of cytokine and chemokine stimulation was performed to investigate effects related to ECM remodelling and modulation of cytokine and chemokine mRNA expression. Results: IHC identified CD4, CCR1, CXCR1 and CXCR2 expression by NP cells. Differential expression profiles were observed for CD4 and CXCR2 in tissue samples from degenerate and infiltrated IVDs. In vitro stimulations of primary human NP cultures with IL-16, CCL2, CCL3, CCL7 or CXCL8 did not identify any modulatory effects on parameters associated with ECM remodelling or expression of other cytokines and chemokines. Conversely, IL-1 was seen to modulate ECM remodelling and expression of all other cytokines and chemokines investigated. Conclusion: This study demonstrates for the first time that NP cells express a number of cytokine and chemokine receptors and thus could respond in an autocrine or paracrine manner to cytokines and chemokines produced by NP cells, particularly during tissue degeneration. However, this study failed to demonstrate regulatory effects on ECM genes and degradative enzymes or other cytokines and chemokines for any target investigated, with the exception of IL-1. This suggests that IL-1 is a master regulator within the IVD and may exert regulatory potential over a plethora of other cytokines and chemokines.